Influence of Pregnancy on Whole-Transcriptome Sequencing in the Mammary Gland of Kazakh Mares - Zhenyu Zhang; Zhixin Lu; Xinkui Yao; Linling Li; Jun Meng; Jianwen Wang; Yaqi Zeng; Wanlu Ren (Animals)
Kazakh mares have drawn significant attention for their outstanding lactation traits. Lactation, a complex physiological activity, is modulated by multiple factors. This study utilized high-throughput sequencing to conduct whole-transcriptome sequencing analysis on the mammary gland tissue of eight Kazakh mares, of which four were pregnant and four were non-pregnant, to systematically reveal the molecular regulatory mechanisms. The results showed differential expression in 2136 mRNAs, 180 lncRNAs, 104 miRNAs, and 1162 circRNAs. Gene ontology functional annotation indicates that these differentially expressed genes are involved in multiple key biological processes, such as the cellular process (BP), metabolic process, and biological regulation. Kyoto Encyclopedia of Genes and Genomes analysis suggests that the differentially expressed genes are significantly enriched in essential pathways such as cytokine–cytokine receptor interaction, the chemokine signaling pathway, and the PI3K-Akt signaling pathway. Additionally, this study constructed a competing endogenous RNA (ceRNA) regulatory network based on the differentially expressed genes (|log2FC| > 1, FDR < 0.05), offering a novel perspective for revealing the functional regulation of the mammary gland. This study compared genomic differences in mammary gland tissue of pregnant and non-pregnant Kazakh mares and identified candidate genes that are closely related to lactation regulation. It found that various genes, such as PIK3CG, IL7R, and SOD2, play central regulatory roles in activating mammary gland functions. These findings provide theoretical support for explaining the molecular mechanisms underlying the mammary gland development of Kazakh mares.